High‐resolution X‐ray fluorescence profiling of hybrid event beds: Implications for sediment gravity flow behaviour and deposit structure. Issue 6 (3rd April 2020) - Hussain, Arif; Haughton, Peter D. W.; Shannon, Patrick M.; Turner, Jonathan N.; Pierce, Colm S.; Obradors‐Latre, Arnau; Barker, Simon P.; Martinsen, Ole J.
Abstract: Hybrid event beds form when turbidity currents that transport or locally acquire significant quantities of mud decelerate. The mud dampens turbulence driving flow transformations, allowing both mud and sand to settle into dense, near‐bed fluid layers and debris flows. Quantifying details of the mud distribution vertically in what are often complex tiered deposits is critical to reconstructing flow processes and explaining the diverse bed types left by mud‐bearing gravity flows. High‐resolution X‐ray fluorescence core scanning provides continuous vertical compositional profiles that can help to constrain mud distribution at sub‐millimetre scale, offering a significant improvement over discrete sampling. The approach is applied here to cores acquired from the Pennsylvanian Ross Sandstone Formation, western Ireland, where a range of hybrid event beds have been identified. Raw X‐ray fluorescence counts are calibrated against element concentrations and mineral abundances determined on coincident core plugs, with element and element log‐ratios used as proxies to track vertical changes in abundances of quartz, illite (including mica), chlorite and calcite cement. New insights include 'stepped' (to higher values) as opposed to 'saw‐tooth' vertical changes in mud content and the presence of compositional banding that would otherwise be overlooked. Hybrid event beds in basin floor sheets that arrived ahead of the prograding fan system have significantly cleaner sandy components than those in mid‐fan lobes. The latter may imply that the heads of the currents emerging from mid‐fan channels entrained significant mud immediately before they collapsed. Many of the H3 debrites are bipartite with a sandier H3a division attributed to re‐entrainment and mixing of a trailing debris or fluid mud flow (H3b) with sand left by the forward part of the flow. Hybrid event bed structure may thus partly reflect substrate interaction and mixing during deposition, and the texture of the bed divisions may not simply mirror those in the suspensions from which they formed.